2015
DOI: 10.3102/0002831214549453
|View full text |Cite
|
Sign up to set email alerts
|

The Internal/External Frame of Reference Model of Self-Concept and Achievement Relations

Abstract: The internal/external frame of reference (I/E) model and dimensional comparison theory posit paradoxical relations between achievement (ACH) and self-concept (SC) in mathematics (M) and verbal (V) domains; ACH in each domain positively affects SC in the matching domain (e.g., MACH to MSC) but negatively in the nonmatching domain (e.g., MACH to VSC). This substantive-methodological synergy based on latent variable models of Trends in International Mathematics and Science Study (TIMSS) data supports the generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 76 publications
4
58
1
4
Order By: Relevance
“…For example, students compare their own skills across different academic domains (e.g., different subjects; Möller and Marsh 2013;Möller et al 2009). External comparison refers to situations in which students compare their own skills in a particular school subject with the perceived skills of other students in the same school subject within their frame of reference (e.g., classmates, Marsh et al, 2015). The source of comparison leads to multidimensionality of ASC, so that students' ASC is hierarchically structured with domain-specific facets according to different subjects of ASC at the bottom and a general ASC at the apex.…”
Section: Conceptualization Of Ascmentioning
confidence: 99%
“…For example, students compare their own skills across different academic domains (e.g., different subjects; Möller and Marsh 2013;Möller et al 2009). External comparison refers to situations in which students compare their own skills in a particular school subject with the perceived skills of other students in the same school subject within their frame of reference (e.g., classmates, Marsh et al, 2015). The source of comparison leads to multidimensionality of ASC, so that students' ASC is hierarchically structured with domain-specific facets according to different subjects of ASC at the bottom and a general ASC at the apex.…”
Section: Conceptualization Of Ascmentioning
confidence: 99%
“…In the UAE, parents tend to heavily rely on school staff and teachers for their involvement, as they contend with the different responsibilities of parents, teachers and schools (Moussa-Inaty and De La Vega 2013). Using the Trends in International Mathematics and Science Study (TIMSS) data to compare student's academic self-concept across Western, Asian and Middle Eastern countries, Marsh et al (2015) revealed some cross-cultural differences where predictions of relationships between math and science achievement and student self-concept were not fully supported by the data from Middle Eastern countries. Analysts also argued that in the UAE many female Emirati college students are not motivated to raise their academic achievements, as they are not under family pressure to work after graduation (Crabtree 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surprisingly, very few studies have explored motivational outcomes in the context of CI, even with regard to STEM reforms where the role of motivational outcomes in predicting STEM career choices is well substantiated (Jansen, Schroeders, & Lüdtke, 2014;Watt & Eccles, 2008). Further attesting to the critical role of motivational variables, achievement is reciprocally associated with students' motivation, as academic self-concepts and interests are highly influenced by previous achievement but also predict later achievement (Marsh et al, 2015;Schurtz, Pfost, Nagengast, & Artelt, 2014).…”
Section: Effects Of Curricular Intensification On Achievement and Motmentioning
confidence: 99%